2015
DOI: 10.1016/j.leukres.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

LFA-1-targeting Leukotoxin (LtxA; Leukothera®) causes lymphoma tumor regression in a humanized mouse model and requires caspase-8 and Fas to kill malignant lymphocytes

Abstract: Leukotoxin (LtxA) is a protein secreted from the oral bacterium Aggregatibacter actinomycetemcomitans. LtxA binds to the β2 integrin lymphocyte-associated function antigen-1 (LFA-1) on human white blood cells (WBCs), resulting in cell death. LtxA is currently under investigation as a novel therapy (Leukothera®) for treating hematologic malignancies and autoimmune diseases. We show here that LtxA has potent in vivo anti-lymphoma activity in mice. LtxA caused complete regression of B-cell tumors and promoted lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…In contrast to myeloid cells, LtxA uses “slow mode” of lymphocyte killing. Killing of malignant lymphocytes requires Fas receptors and caspase 8 in both T and B lymphocytes [62]. In B lymphocytes (JY cells), LtxA caused loss of mitochondrial membrane potential, cytochrome c release, reactive oxygen species release, and activation of caspases 3,7,9 [26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to myeloid cells, LtxA uses “slow mode” of lymphocyte killing. Killing of malignant lymphocytes requires Fas receptors and caspase 8 in both T and B lymphocytes [62]. In B lymphocytes (JY cells), LtxA caused loss of mitochondrial membrane potential, cytochrome c release, reactive oxygen species release, and activation of caspases 3,7,9 [26].…”
Section: Discussionmentioning
confidence: 99%
“…DiFranco et al recently demonstrated that LtxA kills lymphoma cells in a caspase‐8‐dependent manner. The authors then screened a number of receptors and proteins that can activate caspase‐8, and identified the death receptor, Fas, as an essential component in the LtxA‐mediated killing of these cells (DiFranco et al, 2015). The researchers also observed decreased antibody binding when cells were pretreated with the toxin, suggesting that LtxA binds directly with the Fas receptor.…”
Section: Host Cell Interactionsmentioning
confidence: 99%
“…The interaction of LtxA with LFA‐1 and cholesterol appears to initiate an intracellular cascade of events that ultimately leads to apoptosis (Figure 3). While the entire mechanism is not yet known, it is important to note that evidence points to differing pathways in monocytes versus lymphocytes; however, the requirement of LFA‐1 is consistent between both cell types (DiFranco et al, 2012, 2015).…”
Section: Host Cell Interactionsmentioning
confidence: 99%
“…It binds to activated LFA-1 and induces apoptosis by several mechanisms [62]. Leukotoxin shows a tendency to kill leukemic cells in a LFA-1-dependent manner [63] [64]. Whereas normal hematopoietic cells might be partially sensitive, leukotoxin shows preferential activity against active LFA-1 and spares most blood cells.…”
Section: The Effect Of Leukotoxinmentioning
confidence: 99%
“…Whereas normal hematopoietic cells might be partially sensitive, leukotoxin shows preferential activity against active LFA-1 and spares most blood cells. The death of tumor lymphocytes occurred by a Fasdependent mechanism [64]. Besides the advantage of counting with a potential therapeutic tool, working out the mechanism behind leukotoxin's action on LFA-1 leading to cell death, will provide new knowledge linking adhesion to cell fate decisions.…”
Section: The Effect Of Leukotoxinmentioning
confidence: 99%